2020
DOI: 10.3390/s20020480
|View full text |Cite
|
Sign up to set email alerts
|

A Plastic Optical Fiber Sensing System for Bridge Deflection Measurement

Abstract: Deflection is one of the key parameters that reflects the state of a bridge. However, deflection measurement is difficult for a bridge that is under operation. Most existing sensors and measuring techniques often do not meet the requirements for health monitoring for various types of bridges. Therefore, based on changes of optical fiber intensity, a novel sensing system using connected pipes to measure bridge deflection in different positions is proposed in this paper. As an absolute reference, the liquid leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(29 reference statements)
0
2
0
1
Order By: Relevance
“…The capability and good performance of this DFOS for the long-term monitoring of bridge structures have been confirmed by some fatigue tests [169]. Of course, DFOS can also be useful for bridge deflection monitoring [170], and the latest advancement here has been the use of polymer optical fiber sensing (POFS)-based technology to monitor bridge deflection [171]. Since DFOS is less commonly used in practice on structures outside the laboratory, Novák et al [172] successfully demonstrated the potential of using DFOS to detect and monitor traffic-induced crack development in field experiments on bridges with traffic vibrations.…”
Section: Bridge Structure Health Monitoringmentioning
confidence: 78%
“…The capability and good performance of this DFOS for the long-term monitoring of bridge structures have been confirmed by some fatigue tests [169]. Of course, DFOS can also be useful for bridge deflection monitoring [170], and the latest advancement here has been the use of polymer optical fiber sensing (POFS)-based technology to monitor bridge deflection [171]. Since DFOS is less commonly used in practice on structures outside the laboratory, Novák et al [172] successfully demonstrated the potential of using DFOS to detect and monitor traffic-induced crack development in field experiments on bridges with traffic vibrations.…”
Section: Bridge Structure Health Monitoringmentioning
confidence: 78%
“…However, further work is still needed to explore low-cost, high-sensitivity, and high-stability monitoring technologies. [154].…”
Section: Buildingsmentioning
confidence: 99%
“…The experimental results proved that the monitoring system supervised that the 93.9-m-long part of the optical fiber had detected a small elastic strain in the range of as low as 2 μm/m with a spatial resolution of 20 cm. Subsequently, Dong Yang et al [ 154 ] proposed a deflection measurement for bridges based on the plastic optical fiber sensing (POFS) system. As shown in Figure 15 , the system consists of three parts: a connecting tube for connecting to the measuring point, a liquid for filling the connecting tube, and a new plastic optical fiber liquid level sensor.…”
Section: Applications Of Fiber-optic Sensor (Fos) Technologymentioning
confidence: 99%
“…Dada la importancia estratégica de los puentes como nexos de unión, se han realizado numerosos estudios en su monitorización, tanto metálicos como de hormigón (Asadollahi, Huang and Li, 2018;Meng et al, 2018;Marchewka, Ziółkowski and Aguilar-Vidal, 2020;Mousavi et al, 2020;Shao et al, 2020;Yang et al, 2020)(Navarro-Henríquez, 2014) (Peng et al, 2020).…”
Section: Puentesunclassified